2010
DOI: 10.3844/ajassp.2010.447.452
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Reactive Dyes Sorption Enhancement of Rice Hull through Chemical Modification

Abstract: Problem statement: Many studies have been conducted on the removal of either anionic or cationic dyes. However, as a mixture of dyes does commonly exist together in wastewater, therefore it is of great interest to have a material that can remove both types of dyes. Approach: To prepare an inexpensive and efficient sorbent by chemically modifying rice hull for the removal of both basic and reactive dyes. Different chemical modifications were performed on rice hull and a comparison study on the uptake of dyes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Modification with the acids did not improve the removal of MV, and it may be due to the removal of certain soluble organic compounds [52] that favour the removal of MV. It was reported that not all modifications of adsorbent lead to higher adsorption capacities [53].…”
Section: Pre-treatment Of Adsorbentmentioning
confidence: 99%
“…Modification with the acids did not improve the removal of MV, and it may be due to the removal of certain soluble organic compounds [52] that favour the removal of MV. It was reported that not all modifications of adsorbent lead to higher adsorption capacities [53].…”
Section: Pre-treatment Of Adsorbentmentioning
confidence: 99%
“…Hema and Arivoli (2007) used carbonized leaves of Pandanus with concentrated sulphuric acid in the weight ratio of 1:1 (W/V) for removing Congo red, Malachite green and Rhodamine B. Ong et al (2010) compared the efficiency of base-treated rice hull, hydrochloric acid-treated rice hull, quaternized rice hull, citric acid-treated rice hull, nitrilotriacetic acid-treated rice hull and ethylenediamine-modified rice hull for removing cationic dye BB3 and anionic dye RO16 from aqueous solution. Activated carbons were prepared from coconut shell, coir pith and rice husk using 1 M ferric chloride, 1 M trioxonitrate (V) acid, 1 M orthophosphoric acid and 1 M potassium carbonate as the chemical activating reagents for removing blue dye by Adekola and Adegoke (2005).…”
Section: Modifications Of Adsorbentsmentioning
confidence: 99%
“…However, the linear form of pseudo-second-order equation proposed by Ho and McKay [43] was found to be Cucumber peels 111.11 [11] Watermelon seed hulls 57.14 [11] Grape pulp 153.85 [15] Peanut husk 72.13 [46] Spent EDTA-modified rice husk 46.30 [23] Sago waste carbon 4.51 [41] HCL-treated meranti sawdust 120.48 [12] TA-modified bagasse 69.93 [13] NaOH-modified durian leaf powder 125 [14] q e and q t are the amounts of MB adsorbed (mg g -1 ) at equilibrium and at time t (min), respectively; k 1 (min -1 ) is the adsorption rate constant; k 2 (g mg -1 min -1 ) is the rate constant of second-order adsorption; k 1 d (mg/g h) is the intraparticle diffusion rate constant and C gives an idea about the thickness of the boundary layer; a (mg/g h) is the initial sorption rate and b (g/mg) is related to the extent of surface coverage and activation energy for chemisorption able to predict the behavior of the sorption process for all the range of concentrations studied here. The linear plots of t/q t against t (min) gives 1/q e (cal) as the slope and 1/k 2 q e 2 as the intercept, where k 2 (g/mg-min) is the rate constant of the second-order adsorption as shown in Table 8 and Fig.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…These lignocellulosic byproducts possess various advantages, such as being ecofriendly, renewable, less expensive and abundantly available, as compared to commercial adsorbents [18,20]. Studies have also shown that chemical modification of agricultural by-products significantly enhances their ionbinding properties, thereby providing greater flexibility in their applications to a wide range of dyes [21][22][23][24]. However, while agricultural by-products are often presented as low-cost adsorbents, their availability is often region specific.…”
Section: Introductionmentioning
confidence: 99%